Solving vehicle routing problem by using improved genetic algorithm for optimal solution - Mohammed M.A.; Abd Ghani M.K.; Hamed R.I.; Mostafa S.A.; Ahmad M.S.; Ibrahim D.A. (Elsevier B.V., 2023)
Bus transportation; Buses; Cost reduction; Costs; Education; Genetic algorithms; Location; Optimal systems; Routing algorithms; Students; Transportation; Transportation routes; Vehicle routing; Vehicles; Capacitated vehicle routing problem; Crossover operations; Economic interests; Evaluation criteria; Optimal solutions; Transportation cost; Vehicle routing problem; Vehicle Routing Problems; Problem solving